Physical and chemical foundations of the extraction refining of natural uranium - Mukhachev, A.P.; Yelatontsev, D.O.; Kharitonova, O.A. (Вопросы атомной науки и техники, 2022)
The paper presents the results of studies of the physicochemical processes of the extraction and nitric acid purification of uranium salts obtained by the method of precipitation of ammonium uranyl carbonate (AUC) from ore solutions of leaching of uranium and polymetallic ores with their subsequent dissolution in nitric acid. It is shown that the process of extraction on a mixture of tributyl phosphate (TBP) in kerosene makes it possible to obtain high-purity uranium oxide. For the selective extraction of impurities, the process of uranium extraction from the nitric acid medium was carried out with a mixture of TBP and di(2-ethylhexyl) phosphoric acid (DEHPA) in kerosene. The first uranium concentration 40…50 g/L simulated the process of uranium desorption, the second ≤ 100 g/L simulated the process of dissolution of uranium oxide. The study of the uranium extraction made it possible to determine the required number of extraction stages to achieve the minimum uranium content in the raffinate and the maximum extractant capacity, which ensured the specified coefficients of uranium purification from metal impurities (V, Mo, etc.). After extraction, the nitric acid raffinate served as a raw material for the production of a mineral fertilizer – sodium nitrate.